Stress in pregnancy - implications for fetal BDNF in amniotic fluid at birth - Lamadé, Eva; Pedraz Petrozzi, Bruno; Lindner, Ole; Meininger, Pascal; Pisters, Antonia; Gilles, Maria; Witt, Stephanie; Rietschel, Marcella; Dukal, Helene; Schunk, Fabian; Coenen, Michaela; Wudy, Stefan A.; et al. (Neurobiology of Stress, 2024)
Introduction - At the maternal-fetal interface in pregnancy, stress during pregnancy can lead to an increased vulnerability to later psychopathology of the fetus. Potential mediators of this association have scarcely been studied and may include early alterations of fetal brain-derived neurotrophic factor (BDNF). Amniotic fluid is of particular interest for effects on fetal endocrine alterations, as the assessment in amniotic fluid allows for measurements over a time integral. This study hypothesized that maternal psychometrics, socioeconomic status and glucocorticoids are related to BDNF levels in amniotic fluid at birth. The association of fetal BDNF with newborn anthropometrics was tested. - Methods - Women near term who underwent elective cesarean section and their newborns were investigated (n = 37). Maternal psychometrics, socioeconomic status and glucocorticoids (the sum of cortisol and cortisone) in amniotic fluid at birth were analyzed for an association with fetal BDNF in amniotic fluid at birth. Newborn anthropometrics were assessed by length, weight, head circumference and gestational age at birth. - Results - In bivariate analysis, maternal psychometrics and socioeconomic status were not related to fetal BDNF in amniotic fluid at birth. The sum of cortisol and cortisone related to increased fetal BDNF in amniotic fluid at birth (r = 0.745, p < 0.001). BDNF in amniotic fluid was associated negatively with fetal birth weight per gestational age (r = −0.519, p < 0.001), length per gestational age (r = −0.374, p = 0.023), head circumference per gestational age (r = −0.508, p = 0.001), but not with gestational age at birth. In multiple regression analysis, the sum of cortisol and cortisone (p < 0.001) and birth weight per gestational age (p = 0.012) related to higher fetal BDNF levels in amniotic fluid at birth (R2 = 0.740, p < 0.001) when controlling for fetal sex and maternal age. Head circumference per gestational age predicted fetal BDNF with borderline significance (p = 0.058) when controlling for confounders. - Conclusion - Glucocorticoids in amniotic fluid were positively associated with high fetal BDNF at birth, which may be an adaptive fetal response. Maternal psychological variables and socioeconomic status did not link to fetal BDNF. Birth weight and head circumference per gestational age were inversely associated with fetal BDNF at birth, which may represent a compensatory upregulation of BDNF in fetuses with low anthropometrics. Longitudinal studies are needed to assess the role of stress during pregnancy on later offspring development. The analysis of additional fetal growth factors and inflammation upon maternal stress in further biomaterials such as the placenta is warranted, to understand mechanistic alterations of how maternal stress links to fetal development and an increased vulnerability for psychopathology.